Autoimmune cerebellar ataxia associated with anti-leucine-rich glioma-inactivated protein 1 antibodies: Two pediatric cases - Weihua, Zhang; Haitao, Ren; Jie, Deng; Changhong, Ren; Ji, Zhou; Anna, Zhou; Hongzhi, Guan; Xiaotun, Ren (Journal of neuroimmunology, 2022)
To report two pediatric cases of autoimmune cerebellar ataxia associated with the anti-Leucine-rich glioma-inactivated protein 1 (LGI1)antibodies. The clinical features of the two patients were described retrospectively. The indirect immunofluorescence using transfected cells (cell-based assay, CBA) and the rat cerebellum (tissue-based assay, TBA) with the multi-antigen co-plate biochip mosaic techniques were used to detect the antibodies. Clinical and laboratory characteristics were described. Two males were included. The onset ages were 2.7y and 4y, respectively. Patient 1 manifested as isolated acute cerebellar ataxia. Patient 2 had extra-cerebellar symptoms, including seizures, encephalopathy, faciobrachial dystonic seizures(FBDs), and significant cerebellar ataxia. The hyponatremia and tumors were not found. Both of them responded well to the immunotherapy. The autoimmune cerebellar ataxia might be a new phenotype of LGI1-Abs autoimmunity in children.